The generalized localization for multiple Fourier integrals. - Ashurov , Ravshan; Ahmedov, Anvarjon; Mahmud , Ahmad Rodzi (Academic Press Inc., 2010)
In this paper we investigate almost-everywhere convergence properties of the Bochner–Riesz means of N-fold Fourier integrals under summation over domains bounded by the level surfaces of the elliptic polynomials. It is proved that if the order of the Bochner–Riesz means s⩾(N−1)(1/p−1/2), then the Bochner–Riesz means of a function f∈Lp(RN), 1⩽p⩽2 converge to zero almost-everywhere on RN∖supp(f).